НЕАЛКОГОЛЬНАЯ ЖИРОВАЯ БОЛЕЗНЬ ПЕЧЕНИ У БОЛЬНЫХ С ОСТРОЙ СЕРДЕЧНО-СОСУДИСТОЙ ПАТОЛОГИЕЙ - И. Н. Каграманян; А. Л. Хохлов; Е. С. Емельянов (Архивъ внутренней медицины)
To determine the prevalence of fatty liver as in patients with diabetes and implemented risk of chronic hyperglycemia: ischaemic heart disease and stroke. Methods: 1125 people, men — 552 women — 573 with ischaemic heart disease or stroke. Diabetes mellitus — 194, intermediate hyperglycaemia — 87. The age of patients from 54 to 92 years, mean age 69 ± 10.1 years. Results: the differences in the incidence of NAFLD in patients with diabetes and IGT — not found. Acute CVD in patients with both diabetes and with IG recorded during ultrasonic of the liver without NAFLD. Conclusion: the detection rate of NAFLD patients with DM and acute CVD ––13.9%.